Genome-Wide Identification of Circular RNAs in Response to Low-Temperature Stress in Tomato Leaves - Yang, Xuedong; Liu, Yahui; Zhang, Hui; Wang, Jinyu; Zinta, Gaurav; Xie, Shangbo; Zhu, Weimin; Nie, Wen-Feng (Frontiers in Genetics, 2020)
Cold stress adversely affects plant growth and development thereby causing significant crop yield losses. Circular RNAs (circRNAs) are non-coding RNA that function in transcriptional and post-transcriptional gene regulation and play crucial role in abiotic stress responses. Here, the role of circRNAs in low temperature stress responses in tomato was investigated. We generate genome-wide profiles of circRNAs and mRNAs in tomato seedlings grown at 25 ºC room temperature (RT) and 12 ºC low temperature (LT). Our results show that 1,830 circRNAs identified in tomato seedlings in both RT and LT treatments, among which 1,759 were differentially regulated by low temperature treatment. We find that the identified circRNAs are mainly distributed at exons of genes, but less distributed at introns of genes or intergenic regions. Our results suggest that there are 383 differentially expressed circRNAs predicted to function as the putative sponges of 266 miRNA to target 4,476 mRNAs. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis indicate multiple pathways were enriched in both differentially expressed genes induced by low temperature and parental genes of low temperature induced differentially expressed circRNAs, revealing the functions of circRNAs and the corresponding targeted genes in response to low temperature stress. These results suggest that circRNAs may be involved in regulating metabolism (i.e. carbohydrate, amino acid, lipid, energy), signal transduction, and environmental adaption related pathways. Moreover, these circRNAs were predicted to be involved in regulating the expression of various transcription factor families, signal transduction related genes and Ca2+ channel through targeting associated proteins, such as WRKY, NAC, cytochrome P450 and calmodulin binding protein. Taken together, these results shed light on the biological functions of circRNAs in low temperature stress tolerance and provides the potential networks of circRNA-miRNA-mRNA in response to low temperature stress for further investigations in tomato.